Исследовательская деятельность учителя на уроках технологии как приоритетный фактор качества образования - Салыков, А.С. (My University, 2016)
This article is devoted to the research work as the main innovative pedagogical method, which is rather relevant at the modern stage of education development. The result of the research work proves that creative independent activity under the direction of the teacher helps to form the professional competence.
Keywords: technology; professional competence; research work; creative potential